2015
DOI: 10.1063/1.4917022
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced nucleation of carbon dioxide bubbles

Abstract: A detailed experimental study of laser-induced nucleation (LIN) of carbon dioxide (CO2) gas bubbles is presented. Water and aqueous sucrose solutions supersaturated with CO2 were exposed to single nanosecond pulses (5 ns, 532 nm, 2.4-14.5 MW cm(-2)) and femtosecond pulses (110 fs, 800 nm, 0.028-11 GW cm(-2)) of laser light. No bubbles were observed with the femtosecond pulses, even at high peak power densities (11 GW cm(-2)). For the nanosecond pulses, the number of bubbles produced per pulse showed a quadrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(90 citation statements)
references
References 43 publications
1
79
0
Order By: Relevance
“…11,27 Studies on NPLIN of carbon dioxide bubbles and on filtration of solutions have suggested that transient heating of an impurity nanoparticle can cause rapid expansion and collapse of a vapor bubble, which triggers nucleation. 18,19,27,28 The heating mechanism satisfies several observations that the OKE mechanism does not, including the existence of a distinct laser-power threshold, and the fact that some substances do not exhibit NPLIN despite being likely candidates. 19 Absorption and heating would be expected to show little effect of polarization on direction of product nucleation, although further experiments are required to study this systematically.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…11,27 Studies on NPLIN of carbon dioxide bubbles and on filtration of solutions have suggested that transient heating of an impurity nanoparticle can cause rapid expansion and collapse of a vapor bubble, which triggers nucleation. 18,19,27,28 The heating mechanism satisfies several observations that the OKE mechanism does not, including the existence of a distinct laser-power threshold, and the fact that some substances do not exhibit NPLIN despite being likely candidates. 19 Absorption and heating would be expected to show little effect of polarization on direction of product nucleation, although further experiments are required to study this systematically.…”
Section: Resultssupporting
confidence: 53%
“…17 Recent experimental results have pointed towards a mechanism based on heating of trace impurity nanoparticles. 18,19 Since the observation of alignment of urea needles along the electric field of the light is central to understanding the mechanism, we have carried out digital imaging of crystal growth during NPLIN of urea.…”
Section: Introductionmentioning
confidence: 99%
“…55 As outlined in Section 1, the OKE mechanism for NPLIN, based on laser-induced molecule alignment, has been cast into doubt. 37,[42][43][44][45] An alternative mechanism has been put forward, involving transient heating of particles, leading to formation of cavities and pressure shockwaves in the solution. 43,45 This alternative mechanism for NPLIN is very similar to those believed to operate for ultrasound and mechanical shock, and would account for the similarities in the behaviour shown in Fig.…”
Section: Nucleation Mechanismsmentioning
confidence: 99%
“…42,43 An alternative mechanism to explain NPLIN has been described, based on formation of transient vapour cavities due to heating of impurity particles by the laser light. [43][44][45] The objective of the present work was to explore the supersaturation dependence of polymorphism in glycine solutions using different methods for inducing nucleation. The methods used were pulsed laser light (NPLIN), ultrasound and mechanical shock.…”
mentioning
confidence: 99%
“…2, we show the visualization of acoustic phenomena in the bath ( 28 kHz) under different DO supersaturation. Even under the low-intensity ultrasound irradiation, visible-sized acoustic bubbles appear more densely under higher DO supersaturation, indicating that the population of active bubble nuclei increases as DO supersaturation increases [32,33]. For the lower DO-supersaturation cases ( 0.1 and 1.0), bubbles are entrapped via the primary Bjerknes force [34] that arises from a standing-wave pressure field in the bath.…”
Section: Results and Discussion 31 Cavitation Under Do Supersaturationmentioning
confidence: 99%